The Economic Thought of Syeikh al Mutawalli Al-Sya'rawi from His Book of 'Tafsir Al-Sya'rawi' - Mohd Shahid Bin Mohd Noh (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2021)
Syeikh al-Mutawalli al-Sya'rawi is a prominent muslim Egyptian scholar in his era. He had King Hammad Price as an appreciation on his contribution of ideas and thoughts towards islamic spiritual development and yet he became well known in Muslim world, particular in Arab countries through his tafsir lesson, where eventually been written and complied in volume of books, namely as Tafsir al-Sya'rawi. Besides producing the ideas on aqidah, feqh and tasawwuf, he also included in his words some of the economic thought were could be derived from his books and lectures. This paper aims to explore numbers of his economic thought mobilizing the analysis content methodology from his tafsir, particularly in Surah al-Baqarah. As a result, this study finds that he had shown consistent ideas in supportingshari’ah laws in promoting sadaqahandinfaq, sharingrizq, combatting gambling andriba, strengthening zakat roles and enforcing debt etiquette as mentioned in Al-Quran by giving economic reasons behind the elements said.